Relationship between health behaviors and self-reported diseases by public employees - Janaina Maria Setto; Palmira de Fátima Bonolo; Sylvia do Carmo Castro Franceschini
Abstract Introduction: Life habits such as physical activity, leisure, eating habits, stress, smoking, and alcohol consumption can directly affect individuals' health. Objective: This study aimed to investigate the relationship between health behaviors and diseases self-reported by employees of a federal public university in southeastern Brazil. Methods: This cross-sectional study included 815 employees, of whom 347 were teachers and 468 were technical-administrative staff, aged between 20 and 65 years old. Data from this study were collected from a secondary database, from the Health Questionnaire (self-reported health conditions by teachers and technical-administrative employees), and from the institution's Vice Dean of Community Affairs. Among the variables assessed, the relationship between eating habits, physical activity, smoking, alcohol consumption, and self-reported illnesses (chronic diseases and infectious and parasitic diseases diagnosed by a doctor within the last 12 months) was analyzed. Results: The mean prevalence of these diseases among teachers and technical-administrative staff was 3.1 and 2.9, respectively. This study showed a statistically significant association between unhealthy diet and cerebrovascular accidents; between irregular performance of physical activity/sedentary lifestyle and endocrine/nutritional/metabolic and digestive diseases; between overweight and cardiovascular diseases, endocrine/nutritional/metabolic diseases, diabetes mellitus, and hypertension; and between smoking and musculoskeletal diseases. Conclusion: We suggest the adoption of preventative measures and the control of risk behaviors among these employees.